The gross morphology of the stomach of the Malaysian lesser mousedeer (Tragulus javanicus) - Vidyadarayan, M. K.; M. Hilmi; Sirimane, Roy A. (Universiti Pertanian Malaysia, 1982)
The gross morphology of the stomach of the lesser mouse deer is described. Characteristically, the rumen is S-shaped spirally twisted and has large ventral and caudoventral sacs. The omasum is vestigeal and is represented by an area of about (2-3 cm'). Reticulo rumen volume is largPr than for ox and sheep.